The importance of key activation technologies in smart strategy expert: The evaluation of EU countries and Turkey - Melis Çil (Focus on Research in Contemporary Economics, 2020)
This study aims to, in line with the Smart Specialization, evaluate the distribution of KETs, which are used by the EU countries and Turkey, by using country significance indicator. The country significance indicator, which is one of the indicators considered to capture the performance of a country in the production of new technological information, represents the share of exports of goods related to KETs in total manufacturing industry exports. The data set used in the study was compiled from the European Commission Reports and covers the years 2002-2015. The countries included in the data set reported by the European Commission (2018) are EU member states. In addition to these countries Turkey was included in the analysis as a developing economy. To make a general evaluation; in order for Turkey to end foreign trade deficit, to find a place in the global competition and to realize the development successfully by using smart specialization, effective use of Key Activation Technologies is needed.